2011
DOI: 10.2460/javma.239.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic lesions in neonatal foals evaluated for nonophthalmic disease at referral hospitals

Abstract: Ophthalmic lesions were detected in 55.7% of neonatal foals with systemic disease. Acquired ophthalmic disease was more commonly detected than congenital ophthalmic disease. Foals with sepsis were more likely to have uveitis than were foals without sepsis. A complete ophthalmic examination is indicated in neonatal foals evaluated for systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
4
21
1
2
Order By: Relevance
“…The clinical appearance of these cases was similar to previous descriptions of entropion in cattle, sheep, horses, and small animals . Two goats in this study had significant corneal stromal ulcerative defects as a secondary complication to their entropion consistent with previous reports . The goats in this study were affected prior to 1 month of age suggesting the condition may have been congenital.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The clinical appearance of these cases was similar to previous descriptions of entropion in cattle, sheep, horses, and small animals . Two goats in this study had significant corneal stromal ulcerative defects as a secondary complication to their entropion consistent with previous reports . The goats in this study were affected prior to 1 month of age suggesting the condition may have been congenital.…”
Section: Discussionsupporting
confidence: 89%
“…Entropion is a well‐recognized veterinary ophthalmic abnormality diagnosed in dogs, cats, horses, sheep, cattle, and pigs . It most commonly occurs in sheep and dogs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various kinase inhibitors have been investigated for the simultaneous inhibition of both VEGF and PDGF receptors for the treatment of ocular neovascularization [73,74]. A PEGylated aptamer, E10030 selectively inhibits PDGF-β and stimulates striping of pericytes from the endothelial cells [75]. It improves sensitivity of mature vasculature for anti-VEGF treatment.…”
Section: Future Therapiesmentioning
confidence: 99%
“…Therefore, simultaneous administration of anti-VEGF agents along with E10030 may inhibit CNV. In fact, in Phase I clinical trials, 90% of the subjects have observed CNV regression when treated with ranibizumab and E10030, relative to 10% of the patients treated with ranibizumab alone [75,76]. A Phase II clinical study is currently under progress [205].…”
Section: Future Therapiesmentioning
confidence: 99%